ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA AKTIVITAS PROSES PRODUKSI DI DEPARTEMEN AUTOLATHE PADA PT XYZ - Sijabat, Reychandro Eryvan Pardomuan; Welly Sugianto (Computer Science and Industrial Engineering, 2025)
The Autolathe Department is an organizational unit responsible for producing specific products at PT XYZ using CNC lathes. The tasks in this department include machine operation, machine setup, part rework, and deburring/polishing parts, all of which are exposed to sharp objects, chemicals, and extreme dust. The company has implemented safety measures such as introducing Occupational Health and Safety (OHS) during recruitment and providing various types of Personal Protective Equipment (PPE). However, these control efforts have not been fully effective. This study aims to identify risks in all tasks within the Autolathe department using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method and Job Safety Analysis (JSA) method, assess the risk levels, and provide recommendations to the company. The data was collected through documentation, observations, interviews, and discussions with production supervisors who also serve as OHS supervisors. The study found three tasks with high overall risk levels, involving 17 risk variables categorized as extreme or high, such as flying debris, cuts from cutter blades, material pinching, and exposure to chemicals and dust. The study recommends improving the system, including strict sanctions for operators who fail to wear PPE according to Standard Operating Procedures and providing additional PPE.